Relationship between fat distribution ratio and blood pressure in obese adolescents - Henny Marina; Dany Hilmanto; Julistio Tb Djais (Indonesian Pediatric Society, 2008)
Background The incidence of obesity in big cities increasessignificantly. The association between obesity and increased riskof cardiovascular disease and hypertension in adults has beenknown but less information is available in adolescents. Similarly,the relationship between body-fat distribution and cardiovasculardiseases in adolescents is less clear tha that in adults.Objective This study aimed to determine the association betweenbody fat distribution and increased blood pressure in obeseadolescents in Bandung.Methods This cross-sectional study was conducted from June toAugust 2006. Subjects were students aged 15-18 years at highschools in Bandung with body mass index (BMI) measured usingCDC chart 2000 (> P95) and increased blood pressure (> P90)depended on age and gender according to National High BloodPressure Education Program Working Group on High BloodPressure in Children and Adolescents 2004. Waist-to-hip ratio(central fat), and subscapula skinfold-to-triceps skinfold ratio(peripheral fat) were used to measure fat distribution. Correlationbetween body fat distribution and blood pressure was analyzedusing Pearson correlation statistical test.Results Out of 3170 adolescents examined, 34 obese adolescentgirls and 43 obese adolescent boys had increased blood pressure.Correlation between waist-to-hip ratio and systole blood pressurein boys showed by r=0.495; P=0.003 and girls showed r=0.494;P=O.OOl. Correlation between subscapula skinfold-to-tricepsskinfold ratio in boys showed r=0.289; P=0.097 and girls showedby r=0.248; P=0.109.Conclusion Central fat is moderately correlated with increasedblood pressure in obese adolescents.